PERAN PEMERINTAH DALAM PEMBERDAYAAN MASYARAKAT NELAYAN DI DESA CIPARAGEJAYA KABUPATEN KARAWANG - Elvira Ramdayanti; Gilli Argenti; Prilla Marsingga (Institut Pemerintahan Dalam Negeri, 2021)
Empowerment of fishing communities is carried out to improve the welfare and economy of fishing communities through the role of the government. Empowerment is carried out for fishing communities because there are still many fishermen whose lives are on the verge of poverty. The purpose of this research is to find out how the role of local government as a regulator, dynamizer, facilitator, and catalyst in empowering fishing communities in Ciparagejaya Village, Karawang Regency. This study uses a descriptive method with a qualitative approach. Data were analyzed through interview techniques and direct observation of the field. The result of this research is that the government's role for fishermen can be said to be good with the existence of coaching, training, insurance programs, and providing facilities and infrastructure for fishermen in Ciparagejaya village.